2019
DOI: 10.1016/j.ebiom.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel genome-wide associations for suicidality in UK Biobank, genetic correlation with psychiatric disorders and polygenic association with completed suicide

Abstract: Background: Suicide is a major issue for global public health. Suicidality describes a broad spectrum of thoughts and behaviours, some of which are common in the general population. Although suicide results from a complex interaction of multiple social and psychological factors, predisposition to suicidality is at least partly genetic. Methods: Ordinal genome-wide association study of suicidality in the UK Biobank cohort comparing: 'no suicidality' controls (N = 83,557); 'thoughts that life was not worth livin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
148
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(163 citation statements)
references
References 41 publications
8
148
0
7
Order By: Relevance
“…Additionally, gene-based tests found that depressive symptoms among participants in the UK Biobank (n = 99,057) were associated with six genes, including DCC [67]. Another UK Biobank (n = 122,935) gene-based analysis found associations between suicidality and five genes, including DCC [68]. Finally, a GWAS meta-analysis of 135,458 individuals with major depression and 344,901 controls identified 44 genomic loci significantly associated with depression, including an intronic DCC SNP (rs11663393) [69].…”
Section: Depressionmentioning
confidence: 99%
“…Additionally, gene-based tests found that depressive symptoms among participants in the UK Biobank (n = 99,057) were associated with six genes, including DCC [67]. Another UK Biobank (n = 122,935) gene-based analysis found associations between suicidality and five genes, including DCC [68]. Finally, a GWAS meta-analysis of 135,458 individuals with major depression and 344,901 controls identified 44 genomic loci significantly associated with depression, including an intronic DCC SNP (rs11663393) [69].…”
Section: Depressionmentioning
confidence: 99%
“…Most genetic studies of suicidal behaviors are candidate gene analyses that, as demonstrated for other psychiatric traits (7,8), have limited power to detect the key molecular processes of suicide. Recently, several genome-wide association studies (GWAS) of suicidal behaviors have been conducted in large cohorts, identifying several risk loci and confirming a partial genetic overlap with depression (9)(10)(11)(12)(13). This supports the notion that genome-wide investigations are useful for investigating the predisposition to suicidal behaviors.…”
Section: Introductionmentioning
confidence: 65%
“…Initially, the literature search provided 191 articles (PubMed = 97, Scopus = 93) associated to GWAS and suicide. After the methodological inclusion/exclusion criteria, we obtain 21 eligible studies (Table ; Bani‐Fatemi et al, ; Coon et al, ; Erlangsen et al, ; Galfalvy et al, , ; Gross et al, ; Kimbrel et al, ; Laje et al, ; Levey et al, ; Menke et al, ; Mullins et al, ; Perlis et al, ; Perroud et al, ; Pulay & Rethelyi, ; Schosser et al, ; Sokolowski et al, , ; Stein et al, ; Strawbridge et al, ; Willour et al, ; Zai et al, ). Regarding the clinical situation of the individuals included, the behaviors that were mainly studied were SA and SI with frequent psychiatric diagnostics of major depressive disorder or bipolar disorder.…”
Section: Resultsmentioning
confidence: 99%
“…However, we only considered the GWAS with SB (SA, SI, or SC); therefore, the articles of Laje et al (), Menke et al (), and Perroud et al () were excluded from the enrichment analysis. Concerning this, the genes selected derived from 18 reports (Bani‐Fatemi et al, ; Coon et al, ; Erlangsen et al, ; Galfalvy et al, , ; Gross et al, ; Kimbrel et al, ; Levey et al, ; Mullins et al, ; Perlis et al, ; Pulay & Rethelyi, ; Schosser et al, ; Sokolowski et al, , ; Stein et al, ; Strawbridge et al, ; Willour et al, ; Zai et al, ). These eligible genes were located in chromosomes 1–22, having: (a) nine genes the Chr6, (b) eight genes the Chr1, Chr9, and Chr10, (c) seven genes the Chr2 and Chr8, (d) six genes the Chr3 and Chr14, (e) five genes the Chr4, Chr7, and Chr13, (f) four genes the Chr5, Chr11, (g) Chr12 and Chr15, (h) three genes the Chr17 and Chr18, (i) two genes the Chr16, and (j) one gene the Chr19, Chr20, Chr21, and Chr22, more detail see Table S1.…”
Section: Resultsmentioning
confidence: 99%